The resistance mechanisms of bacteria against ciprofloxacin and new approaches for enhancing the efficacy of this antibiotic - Shariati, Aref; Arshadi, Maniya; Khosrojerdi, Mohammad Ali; Abedinzadeh, Mostafa; Ganjalishahi, Mahsa; Maleki, Abbas; Heidary, Mohsen; Khoshnood, Saeed (Frontiers in Public Health, 2022)
Ciprofloxacin (CIP) is an antibiotic agent in the fluoroquinolone (FQ) class and is used to treat a wide variety of infections, including chronic otorrhea, endocarditis, lower respiratory tract, gastrointestinal, skin and soft tissue, and urinary tract infections for around three decades. The primary mechanism of action of CIP is the prevention of DNA replication by inhibiting the A subunit of DNA gyrase and by an additional effect on cell wall compounds. CIP attains therapeutic concentrations in most tissues and body fluids with a low potential for adverse effects and is available in intravenous and oral formulations. While this antibiotic has exceptional characteristics, over the years, CIP resistance has increased in different bacteria such as Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Salmonella typhi. The emergence of CIP-resistant pathogens indicates the need for discovering new synergisms and derivatives of this drug. To this end, combining CIP with various antibacterial agents such as antibiotics from different classes, nanoparticles, natural products, and photodynamic therapy could increase the efficacy of CIP against multi-drug resistant isolate and biofilm community of microorganisms. This review concentrates on the structure, mechanisms of action and resistance, epidemiology of resistance, synergisms, and clinical usages of CIP.